2014
DOI: 10.1002/adfm.201401390
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Direct Laser Written 3D Topographies on Proliferation and Differentiation of Osteoblast‐Like Cells: Towards Improved Implant Surfaces

Abstract: topographies might on the long run guide the design of novel implants with decreased implant failure rates, if osteoblastic functionality is simultaneously secured by the structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 39 publications
1
24
0
1
Order By: Relevance
“…[ 134 ] They fabricated structures built of 12 µm high posts, arranged on different grids and different post distances, with connecting thin rods in various ways ( Figure 9 a). Hohmann et al have shown that topographic parameters have a distinct infl uence on proliferation and morphology of osteoblast-like SaOs-2 cells.…”
Section: Interaction Of Cells With Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 134 ] They fabricated structures built of 12 µm high posts, arranged on different grids and different post distances, with connecting thin rods in various ways ( Figure 9 a). Hohmann et al have shown that topographic parameters have a distinct infl uence on proliferation and morphology of osteoblast-like SaOs-2 cells.…”
Section: Interaction Of Cells With Scaffoldsmentioning
confidence: 99%
“…They were interested in the role of nuclear stiffness and Adv. [ 134 ] Copyright 2014, John Wiley and Sons. 2015, 3, 1488-1507 www.MaterialsViews.com www.advopticalmat.de Figure 9.…”
Section: Interaction Of Cells With Scaffoldsmentioning
confidence: 99%
“…Two‐photon polymerization based 3D printing technology is a newly developed direct laser writing (DLW) technology that can construct structures with sub‐micrometer resolution at a scan speed over 10 000 µm s −1 in three dimensions . During the past several years, similar technology has gained great interests from researchers due to the potential applications in biological engineering, physical study, and so on. In this work, we have successfully applied this 3D printing technology in fabricating pillar structures, singly, doubly, and triply re‐entrant structures (Figure S1, Supporting Information).…”
mentioning
confidence: 99%
“…The first studies on cells were performed on rather concise 3D scaffolds that consisted of a single material ( Figure A). Hohmann and von Freymann investigated the proliferation of osteoblast‐like cells on different 3D topographies and found that 3D culturing in square grids enhanced the proliferation up to 170% with respect to hexagonal structures or unstructured growth substrates . This indicates that the 3D adhesion geometry can influence cell cycle progression.…”
Section: Direct Laser Writing For Cell Culturementioning
confidence: 99%